APLIKASI KUIS ISLAMI BERBASIS MOBILE - Masrizal Masrizal; Putri Yunita; Ridarmin Ridarmin; Sukri Adrianto; Akhmad Sidiq (JTIK (Jurnal Teknik Informatika Kaputama), 2022)
Islamic Religious Education is a very important lesson for Muslims. In general, one of the factors for the lack of interest in children in learning Islam at school is the material presented in book media which only displays text and pictures, so that some children get bored quickly in learning. On the other hand, children are more likely to play games that are less useful than learning Islam, resulting in a lack of children's knowledge about Islam. To overcome this, a children's education quiz approach was carried out by designing an Islamic Quiz Application. This application is built using the React-Native framework and an Android smartphone to run the application. The Islamic Quiz application is an educational quiz for children that provides questions about Islam such as prayer, fasting, zakat, and hajj. To complete the game, the user must answer the questions that have been provided. Keywords: Application, Islamic Quiz, React-Native, Android Smartphone Pendidikan Agama Islam merupakan pelajaran yang sangat penting bagi umat beragama Islam. Pada umumnya, salah satu faktor kurangnya minat anak dalam belajar agama Islam disekolah yaitu materi-materi yang disajikan pada media buku yang hanya menampilkan tulisan dan gambar, sehingga membuat sebagian anak cepat bosan dalam belajar. Disisi lain, anak yang lebih cenderung bermain game yang kurang bermanfaat daripada belajar agama Islam, sehingga mengakibatkan kurangnya ilmu pengetahuan anak tentang Islam. Untuk mengatasi hal tersebut, maka dilakukan pendekatan kuis edukasi anak dengan merancang sebuah Aplikasi Kuis Islami. Aplikasi ini dibangun dengan menggunakan framework React-Native dan smartphone Android untuk menjalankan aplikasinya. Aplikasi Kuis Islami merupakan kuis edukasi anak yang menyediakan pertanyaan-pertanyaan seputar islami seperti materi shalat, puasa, zakat, dan haji. Untuk menyelesaikan permainannya, user harus menjawab pertanyaan-pertanyaan yang telah disediakan. Kata Kunci : Aplikasi, Kuis Islami, React-Native, Smartphone Android